From baby to adult: ontogenetic series of nine species of Ophiuroidea from Atlantic Southwestern - Borges, Michela; dos Santos Alitto, Renata Aparecida; Zacagnini Amaral, Antonia Cecília (Revista de Biología Tropical, 2015)
The post-metamorphic stage is essential in the life history of marine invertebrates. During this period, animals are more vulnerable and suffer high mortality, which influences the distribution and abundance of adult populations. It is also during this period that major morphological changes happen in the individuals, complicating their taxonomic identification. The juvenile ophiuroids dominate the meiofauna in certain times of the year and at some places. However, they are ignored by most ecological studies due to identification difficulties. Here we describe the ontogeny of nine deep-sea species from the Southeast and South regions of Brazil, with the first record of morphological modifications for eight of them. Most organisms were collected 60 to 800 m deep, between December 1997, January, 1998 and March, 1998, during the REVIZEE-Score South / Benthos program. We also included additional material from the Zoology Museum of Unicamp (ZUEC). For descriptions and identifications of the different stages, the specimens were dried and photographed. The juveniles were identified by “backwards” process through the growth series of adults to smaller individuals, a backwards method that was successful in previous studies. Some individuals were mounted on aluminum stubs for scanning electron microscopy. The species were: Ophiacantha pentacrinus (Ophiacanthidae), Ophiomastus satelitae, Ophiomusium acuferum, Ophiomusium eburneum, Ophiomisidium tommasii, Ophiura ljungmani, Ophiura clemens (Ophiuridae), Amphiura complanata (Amphiuridae) and Ophiothrix rathbuni (Ophiotrichidae). Many species could be identified since their most juvenile stage. Some structures remain almost unaltered during the whole life.